ELECTRIC VEHICLE CHARGING STRATEGIES: ENHANCING LOAD FORECASTING WITH EMERGENCY RESPONSE - Xu , Tao Ming; Wang, Xiao Hui (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
Substations play a crucial role in the electrical power infrastructure, and ensuring their reliable operation is of paramount importance. Recent substation accidents and failures have raised significant concerns regarding the safety and stability of the power supply. To address these challenges, the majority of domestic power system substations have adopted intelligent preventing maloperation protection systems. While these systems have proven effective in enhancing safety, certain operational issues persist, such as real-time monitoring of operation ticket implementation and tracking of location data for relevant power equipment and facilities. These limitations can lead to operational inefficiencies and reduced stability and reliability of the power system. In response to these challenges, there is a growing need for a high-performance substation integrated smart preventing maloperation system. This system would not only provide realtime monitoring and tracking capabilities but also significantly reduce operational pressure on substation operators by simplifying complex tasks within the power system. The research and design of such a system are vital to improving the overall safety and efficiency of substation operations. This paper aims to address the existing problems in substation operation and design a comprehensive integrated smart preventing mal-operation system that leverages advanced technology to enhance operational performance and safeguard the power supply.